2018
DOI: 10.3390/nu10081087
|View full text |Cite
|
Sign up to set email alerts
|

Tetragonia tetragonoides (Pall.) Kuntze (New Zealand Spinach) Prevents Obesity and Hyperuricemia in High-Fat Diet-Induced Obese Mice

Abstract: Tetragonia tetragonoides (Pall.) Kuntze, called New Zealand spinach (NZS), is an edible plant used in salad in Western countries and has been used to treat gastrointestinal diseases in traditional medicine. We examined the anti-obesity and anti-hyperuricemic effects of NZS and the underlying mechanisms in high-fat diet (HFD)-induced obese mice. Mice were fed a normal-fat diet (NFD); high-fat diet (HFD); HFD with 75, 150, or 300 mg/kg NZS extract; or 245 mg/kg Garcinia cambogia (GC) extract. NZS decreased body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 33 publications
0
22
0
1
Order By: Relevance
“…Obesity is a major global health concern and is characterized by an imbalance between food intake and energy expenditure which causes excessive accumulation of fat in blood, adipose tissue, and liver (de Freitas Junior and de Almeida, 2017; Lee et al, 2018). Obesity is an important risk factor for type 2 diabetes, cancer, and cardiovascular diseases (Grigoraş et al, 2018).…”
Section: Obesitymentioning
confidence: 99%
“…Obesity is a major global health concern and is characterized by an imbalance between food intake and energy expenditure which causes excessive accumulation of fat in blood, adipose tissue, and liver (de Freitas Junior and de Almeida, 2017; Lee et al, 2018). Obesity is an important risk factor for type 2 diabetes, cancer, and cardiovascular diseases (Grigoraş et al, 2018).…”
Section: Obesitymentioning
confidence: 99%
“…In our previous studies, TTK was found rich in polyphenol (5.88 ± 0.32 mg/g) and flavonoids (4.34 ± 0.23 mg/g), and 6-methoxy-kaempferol-3-O-β-d-glucosyl(1" → 2")-β-d-glucopyranosyl-(6""-(E)-caffeoyl)-7-O-β-d-glucopyranoside (0.53 ± 0.003 mg/g), 6-methoxyflavonols (2-53 mg/g), and caffeic acid (0.32 ± 0.01) were detected as index compounds [13,17,18]. TTK was reported to prevent obesity and hyperuricemia in obese mice induced by a high-fat diet [19], improve the energy and glucose metabolism in estrogen-deficient rats [13], and increase the anti-inflammatory activity [17]. Moreover, it has antidepressant activity with increasing serotonin concentrations by decreasing the serotonin reuptake activity [20].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Chen, Li, Wu, Li, and Ma (2019) and Chen et al (2013) reported that lemon water and rutin exhibited urate lowering potential in a similar fashion. Previously, many natural products as well as their bioactive compounds are reported to inhibit XOD enzyme potently (Hongyan et al, 2016; Jhang et al, 2016; Kumar et al, 2018; Lee, Kim, Yuk, & Kim, 2018; Lee, Kim, Yuk, Lee, & Kim, 2018; Li et al, 2017; Liu et al, 2019; Mehmood, Zhao, Wang, Nadeem, et al, 2019; Peng, Lin, Zhao, & Sun, 2019; Wan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Genome‐wide association studies reported that around 90% hyperuricemia patients exhibit under‐excretion of uric acid. The reabsorption and excretion of uric acid handle by multiple transporters in the intestine and renal tissues such as; URAT1, GLUT9, and breast cancer resistance protein or ATP‐binding cassette, subfamily G, 2 (BCRP, ABCG2) (Ichida et al, 2012; Lee, Kim, Yuk & Kim, 2018; Lee, Kim, Yuk, Lee, et al, 2018, 2019).…”
Section: Discussionmentioning
confidence: 99%